Mycocoenologic study of the macrofungi on the forest of Jbel elbir (Aïn Draham, Jendouba, Tunisia) - Ben Hassine Ben Ali, Mourad; Aschi-Smiti, Samira; Ben, Mourad; Ben, Hassine (African Journal of Ecology, 2013)
Macrofungi have important functions in forest ecosystems. It is essential to have information about these species to ensure proper management of such ecosystems. Due to the importance of forestry in Tunisia and the lack of information on fungal communities, this study was conducted in North Western of Tunisia. The objective was to enumerate macrofungal diversity in relation to various environmental factors. In total, 158 fruiting bodies were collected and 60 species were identified. Among them, 39 species are mycorrhizal. A fruiting body is the first visible appearance of the spore-bearing surface until its disintegration. More fruiting bodies were found on the eastern slopes than on the western slopes. This reflects the distribution of tree species and soil type. Almost all fungal species were collected from soils of moderate acidity (pH 4–pH 5), 5 species from soils with low acidity (pH 5–pH 6.8), and only 3 species from soils with high acidity (pH < 4). The majority of fruiting bodies occurred in soils with a percentage of organic matter ranging from 1 to 5 and a phosphorus content ranging from 15.1 to 20 ppm.
Keywords: Altitude; exposure; Macrofungi; mycocoenology; organic matter; pH; Tunisia

The influence of Pinus radiata, Quercus suber, and improved pasture on soil chemical properties - Noble, A D; Little, I P; Randall, P J (AUSTRALIAN JOURNAL OF SOIL RESEARCH, 1999)
Soil acidification and related land degradation issues are assuming increasing importance in Australia and challenging the concept of sustainability of current land management systems. In this study, the impacts of tree plantations of 2 species and permanent pasture on soil chemical properties are compared. Soil samples were collected from the top 50 cm (0-5, 5-10, 10-15, 15-20, 20-30, and 30-50 cm depths) from 3 adjacent sites carrying pasture and monocultures of Pinus radiata (radiata pine) and Quercus suber (cork oak) on a deep-surfaced yellow podzolic soil, and differences in soil pH and other soil chemical properties were examined. In the surface 0-5 cm, pH was similar at all 3 sites. Below that depth, soil pH was significantly lower and exchangeable Al greater under the cork oak stand than at the other 2 sites. Consistent with a decrease in soil pH there was significantly less exchangeable Ca under cork oak. Also, less clay was observed under the cork oak stand and this is taken as evidence of the degradational impact of soil acidification. An estimate of Ca in the top 50 cm of the soil implies considerable loss of Ca under oak, probably by leaching and loss of litter down the slope. Evidence is presented to show that there has been more Fe and Al movement under oak than under pasture and pine, this being ascribed in part to the greater Al and Fe mobilising capacity of the water-soluble component extracted from freshly fallen leaf litter of oak. The Fe and Al composition of the oxalate extract from concretionary material at 10-30 cm under oak is consistent with a process similar to podzolisation. Pseudogleying of Fe and Al may have accompanied the leaching of bases from the system and a reduction of pH.
Keywords: Acidification; clay cont; exchangeable cations; pH

Effects of fire on soil carbon and nitrogen in a Mediterranean oak forest of Algeria - Rashid, G H (Plant and Soil, 1987)
The effects of wildfire on the dynamics of pH, organic C, total and mineral N and in vitro C and N mineralization were investigated in the soil under oak (Quercus suber L.) trees. Soil samples were taken from 5 to 21 months subsequent to the fire. The pH increased sharply in the burned surface soil (0-5 cm) taken 5 months after the fire and dropped only by half a unit over 14 to 21 months. However, at greater depth (5-15 cm), the burned soil was more acidic than the adjacent unburned soil up to 9 months following the fire, and thereafter its pH rose only slightly above that of the unburned soil. There were sharp rises in the concentration of organic C, total and mineral N in addition to in vitro mineralization activities in the burned surface soil collected 5 months after the fire; these dropped off in the subsequent samples approaching or falling below the values obtained in the unburned surface soil after 21 months. At a depth of 5-15 cm only slight or no increases over unburned soil were evident.
Keywords: Carbon; forest soil; mineralization; nitrogen; pH; Wildfire